The Definition of “Concept” in Cognitive Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents general information about the concept in cognitive linguistics. Concepts are considered key phenomena in cognitive linguistics, cultural linguistics, linguistic conceptology, and other linguistic disciplines within the anthropocentric paradigm. A concept is defined as a mental structure that reflects the interrelationships of language, thought, and culture. It plays a vital role in the organization of knowledge, the categorization of information, and communication processes.